2019
DOI: 10.2478/jolace-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Novice Teachers of English as a Foreign Language in the Czech Republic and their Drop-Out Intentions

Abstract: Problems with staffing play a crucial role among factors influencing the quality of English language teaching at Czech primary and lower secondary schools. Since 1990 the shortage of teachers of English as a foreign language has been repeatedly reported by the Czech School Inspectorate. The shortage is largely caused by the reluctance of English language teacher education study programme graduates to accept teaching positions at primary and lower secondary schools. A drop-out syndrome in the early stages of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Among those tensions, some of the tensions are arguably a common phenomenon among novice teachers, even before the pandemic. For instance, aligned with other studies that have welldocumented how hard it is to be a novice teacher (e.g., Hanušová et al, 2019;Nguyen & Dao, 2019;Tan et al, 2015), some participants mentioned tensions between "university ideology vs field practicality" and "imagined teaching life vs reality". When those collided, the participants needed to negotiate to bridge their prior views into a practical identity (Pravita & Kuswandono, 2021).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Among those tensions, some of the tensions are arguably a common phenomenon among novice teachers, even before the pandemic. For instance, aligned with other studies that have welldocumented how hard it is to be a novice teacher (e.g., Hanušová et al, 2019;Nguyen & Dao, 2019;Tan et al, 2015), some participants mentioned tensions between "university ideology vs field practicality" and "imagined teaching life vs reality". When those collided, the participants needed to negotiate to bridge their prior views into a practical identity (Pravita & Kuswandono, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…When left unattended, tensions will cause burnout and affect novice teachers' well-being (Cendra, 2019;Xu, 2013). A study done by Hanušová et al (2019) further supports this as they found that novice teachers are the most vulnerable group to this problem. If this is not deliberately addressed, it will contribute to teacher attrition as novice teachers will leave their teaching careers entirely (Whalen et al, 2019).…”
Section: Tensions Of Novice Teachersmentioning
confidence: 90%
See 1 more Smart Citation